1973
DOI: 10.1111/j.1471-0528.1973.tb16043.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Gonadotrophins in Relation to Multiple Pregnancy in Nigeria

Abstract: Summary Serum levels of follicle stimulating hormone (FSH) and luteinizing hormone (LH) were measured daily for 10 days from the 7th day of the menstrual cycle in 15 healthy Yoruba women, six of whom had singleton infants, seven of whom had had one set of twins, and two of whom had had two sets of twins. Mean FSH levels were higher at the peak and for four days before and after the peak in women who had had twins, compared to those who had had singletons, and higher still in the women who had had two sets of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 8 publications
(1 reference statement)
2
23
0
Order By: Relevance
“…For seminoma, these comparisons suggested independent effects of both birth order and sibship size, although only the latter, which was stronger, gave significant results. The only previous study examining the risks by birth order allowing for sibship size (Morrison, 1976) Dizygotic twinning may be associated with high maternal gonadotrophin levels (Milham, 1964;Nylander, 1973). On the hormonal hypothesis one might therefore expect that testicular cancer would occur more often in men who were twins.…”
Section: Discussionmentioning
confidence: 99%
“…For seminoma, these comparisons suggested independent effects of both birth order and sibship size, although only the latter, which was stronger, gave significant results. The only previous study examining the risks by birth order allowing for sibship size (Morrison, 1976) Dizygotic twinning may be associated with high maternal gonadotrophin levels (Milham, 1964;Nylander, 1973). On the hormonal hypothesis one might therefore expect that testicular cancer would occur more often in men who were twins.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers of spontaneous DZ twins have a higher incidence of multiple ovulations and several studies report an increased concentration of folliclestimulating hormone (FSH) during their menstrual cycle. 15,16 FSH release is controlled by a complex feedback mechanism from the ovary. Genes in the pathway controlling the synthesis, release and activity of FSH are therefore good candidates for increased DZ twinning frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Milham (1964) suggested a relation between gonadotropins and dizygotic twinning rate; a high twinning rate is related to a high blood gonadotropin level (Nylander, 1973). Soma et aL (1975) reported significantly lower plasma gonado-tropin levels in Japanese women than in Nigerian women, who, as reported by Nylander (1973), had a high frequency of twinning. Soma et aL (1975) suggested that the low dizygotic twinning rate in Japanese women might be related to their low output of gonadotropin.…”
Section: Discussionmentioning
confidence: 77%
“…Such geographical cline of multiple birth rates in Japan was also seen in dizygotic twinning rates, which was higher in the northeast than in the southeast (Imaizumi and Inouye, 1979). Milham (1964) suggested a relation between gonadotropins and dizygotic twinning rate; a high twinning rate is related to a high blood gonadotropin level (Nylander, 1973). Soma et aL (1975) reported significantly lower plasma gonado-tropin levels in Japanese women than in Nigerian women, who, as reported by Nylander (1973), had a high frequency of twinning.…”
Section: Discussionmentioning
confidence: 82%